(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the success rate of transabdominal and transvaginal surgical repair of vesico-vaginal fistulae(VVF). Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Departments of Urology & surgery at Peoples University of Medical and Health Sciences Hospital Nawabshah from December 2013 to May 2016. Materials and Methods: Patients were selected on exclusion and exclusion criteria. Cases of Vesico-vaginal Fistulae (VVF) were included after a detailed history, clinical examination and investigations. Examination under anesthesia and cystoscopy were performed. Cases with genitor urinary pelvic malignancies, uretero vaginal fistulae, urethro vaginal fistulae, ocomplex fistulae involving intestine were excluded. Two groups A & B were made on the basis of approach of repair. In group A vaginal approach was opted to repair uncomplicated low fistulae. In group-B abdominal approach was opted to repair high vesico vaginal fistulae . Results were noted postoperatively and data was analyzed. Results: This 30 months study included 52 female patients, 30 cases in group A and 22 cases group B. . Mean age was 37 years SD± 5 and a range of 22 to 53 in group A while in group B mean age was 34.6 years SD± 4.I and a range of 23 to 55. Mean post operative hospital stay was 6 days in group A while it was 10 in group B. Failure in terms post operative persistent urinary leakage was detected in 4(12 %) in group A while it was observed in 3(13%) cases in group B. consequently success rate of vaginal approach was 88% and that of abdominal approach was 87%. Conclusion: Both vaginal and abdominal approaches to repair low and high vesico vaginal fistula respectively, are almost equally successful at a rate of 88% and 87% respectively.